The Impact of the Pancasila Student Profile Strengthening Project on Political Literacy and Civic Knowledge among Senior High School Students - Azis, Marwiah; Hashim, Shahrin Bin; Muhajir, Muhajir; Suardi, Suardi (Universitas of Muhammadiyah Makassar, 2025)
Students’ understanding of political literacy and civic knowledge remains relatively low, as observed among 11th-grade students at SMA Negeri 3 Takalar. This low level of understanding highlights the need for more contextual and character-oriented learning strategies. This study aims to examine how the implementation of the Pancasila Student Profile Strengthening Project (P5) can improve students’ political literacy and civic knowledge. It also seeks to identify the supporting and inhibiting factors in the project’s implementation, analyze the implications for students’ understanding, and propose solutions to the identified challenges, particularly by focusing on the enhancement of critical thinking dimensions. The research employed a mixed methods approach with a qualitative-dominant emphasis. Data were collected through questionnaires, observations, interviews, and documentation. Quantitative respondents were selected via simple random sampling, while qualitative informants were chosen purposively. Data analysis was conducted qualitatively through data reduction, presentation, and conclusion drawing, and quantitatively through verification and percentage analysis of the questionnaire data. The findings indicate that the implementation of P5 significantly contributes to improving students' understanding of political systems, their ability to analyze political information, and their engagement with social and political issues. Furthermore, the project enhances students’ critical thinking, argumentation, and collaboration skills. In conclusion, P5 proves to be an effective approach in enhancing political literacy and civic knowledge while also fostering active and reflective citizenship among students.